Pendampingan Literasi AI Akademik Berbasis NotebookLM bagi Komunitas Pemerhati Publikasi Ilmiah dalam Meningkatkan Produktivitas Penulisan Karya Ilmiah - Iswanti Iswanti; Dadi Dadi; Netty Nurdiyani; Sri Astuti; Supriyati; Suryono; Wahyu Sulistiyo; Danu Angga Vebriyanto; Filda Hulwani Dewi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2026)
The rapid advancement of Artificial Intelligence (AI) has created new opportunities to support academic activities, particularly in scientific writing and literature review. This community service program aimed to improve academic AI literacy through training and mentoring on the use of NotebookLM for members of a scientific publication community consisting primarily of final-year university students. The activity was conducted at Politeknik Negeri Semarang, using a participatory mentoring approach consisting of needs assessment, pretest, interactive training, guided practice, mentoring, and evaluation. Initial evaluation showed that approximately 80% of participants had never used NotebookLM before the training. After the mentoring program, participants successfully utilized NotebookLM to summarize scientific articles, analyze journal content, generate presentation materials, create infographics, and organize literature more efficiently. The activity also increased participants' awareness of ethical AI utilization in academic writing. The program demonstrates that NotebookLM can function as an effective academic AI assistant to improve scientific literacy and writing productivity among university students. This mentoring model may serve as an alternative strategy for strengthening AI literacy in higher education.